Strategic Directions of Strengthening Competition on Higher Education Market of Georgia - Lasha, Tabatadze (European Scientific Journal, ESJ, 2016)
In the present article the results of wide scale research for studying and analyzing the competition issues of Higher Education Market of Georgia, which is made by the author independently in 2015 under the framework of dissertation survey are reviewed. It contents detail description of activities needed for collecting and analyzing information to develop a research paper of Georgian Higher education market, which includes three level of higher educatioin institutions (University, Teaching University and College). The article presents the research report and its comparative and critical analyze taking under consideration the experience of Baltic and European countries.